2020 IEEE Frontiers in Education Conference (FIE) 2020
DOI: 10.1109/fie44824.2020.9274144
|View full text |Cite
|
Sign up to set email alerts
|

Computing degree apprenticeships: An opportunity to address gender imbalance in the IT sector?

Abstract: This paper explores the potential for new workbased apprenticeship degrees to encourage more women into computing degrees and the IT sector. In the UK, women are currently under-represented on computing courses. Meanwhile the IT industry requires more computing graduates, in general, and specifically more highly skilled women to create appropriate products and systems. The UK has recently introduced apprenticeship computing degrees, where the apprentice is a work-based employee. In some models, apprentices spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Previous studies have indicated that IT apprentices have some technical background (Taylor-Smith et al , 2019), however there is a variation in the level of technical skills apprentices have (Somerville et al , 2020). This raises the question of whether the requirement for specific technical skills steers away those with limited technical backgrounds, including women who are more likely to develop an interest in computing later than men (Smith et al , 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that IT apprentices have some technical background (Taylor-Smith et al , 2019), however there is a variation in the level of technical skills apprentices have (Somerville et al , 2020). This raises the question of whether the requirement for specific technical skills steers away those with limited technical backgrounds, including women who are more likely to develop an interest in computing later than men (Smith et al , 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Non-traditional apprenticeships and gender Smith et al (2020) argued that computing degree apprenticeships can be used a lever to address gender imbalance in the IT sector in the UKa sector that to date has been maledominated. Crawford Lee and Moorwood (2019) propose that degree apprenticeship programmes offer employers a mechanism to address gender gaps and discrimination.…”
Section: Navigating Gender and Social Justice In Ifsmentioning
confidence: 99%
“…Smith et al. (2020) argued that computing degree apprenticeships can be used a lever to address gender imbalance in the IT sector in the UK – a sector that to date has been male-dominated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, Smith et al also explore to what extent these new programs help to address the gender imbalance in computing. They conducted a survey at five UK institutions and found that the degree-level apprenticeships themselves may not directly help to address the gender imbalance, but make several suggestions to improve the gender imbalance going forward, such as by advertising apprenticeships directly to women, as well as more widely [31].…”
Section: Related Workmentioning
confidence: 99%